COMPARISON OF THE EFFECTS OF LOCAL APPLICATION OF HYDROXYAPATITE GRAFT SOAKED WITH ALENDRONATE SOLUTION AND PURE HYDROXYAPATITE GRAFT IN THE MANDIBLE OF OVARIECTOMIZED RATS - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2011)
This study aimed to investigate whether local delivery of alendronate could improve bone formation and decrease bone resorption after hydroxyapatite grafting in ovariectomised rat mandibular defects. Thirty-six female Wistar rats were divided into control and experimental groups. Both groups were ovariectomised. After two months a surgical defect was created on the vestibular side of their mandible. In the experimental group, hydraxyapatite graft soaked with alendronate solution was placed in the bone defect, and in the control group hydroxyapatite graft soaked with physiological saline was used. Both groups were divided into 3 subgroups: 2-, 4-, and 8-week follow-up groups. Each of the groups consisted of 6 rats. The animals were killed at the end of the designated periods. The number of osteoclasts and the amount of new bone formation were evaluated and compared. Eight weeks after surgery, the experimental group had more bone formation than the control group but it was not statistically significant. The number of osteclasts was increased significantly in the 4(th) week compared to the 2(nd) week and decreased significantly in the 8(th) week compared to 4(th), week in both groups. Local application of a single dose of alendronate did not have a decreasing effect on the number of osteoclasts between the second and fourth week. Although hydroxyapatite graft soaked with alendronate solution showed a trend towards better performance for bone formation at the 4(th) week, no statistically significant intergroup difference was found. Biotechnol. & Biotechnol. Eq. 2011, 25(3), 2513-2521
Keywords: alendronate; local application; ovariectomized rat; MUCOPERIOSTEAL FLAP SURGERY; POSTMENOPAUSAL WOMEN; ORAL ALENDRONATE; BONE-FORMATION; RESORPTIVE PHASE; BISPHOSPHONATE; DELIVERY; PREVENTS